The influence of children’s emotional comprehension on peer conflict resolution strategies - Cao, Yanfei; Wang, Haowei; Lv, Yaojian; Xie, Dongjie (Frontiers in Psychology, 2023)
Peer conflicts commonly happen in children’s daily interaction, and strategies they employed to deal with the conflicts have an impact on peer conflict resolution. It has been illustrated that children’s understanding of emotion plays an important role in social communication. However, there is little research focusing on the relation between emotional comprehension and peer conflict resolution strategies. In this study, 90 children of 3 to 6 finished the Test of Emotional Comprehension, and their preschool teachers were required to complete the Conflict Resolution Strategy Questionnaire, which scored each child’s conflict resolution strategies. The results showed that: (a) the preference of conflict resolution strategies differed in age, and girls tended to adopt positive strategies; (b) children’s emotional comprehension grew with age; and (c) children’s conflict resolution strategies and emotional comprehension were closely related. Children’s emotional comprehension can positively predict the overall conflict resolution strategies and negatively predicted negative strategies, whereas mental emotional comprehension can positively predict positive strategies. The factors affecting children’s emotional comprehension and conflict resolution strategies, and their relationship were discussed in depth.